2010
DOI: 10.1590/s1807-59322010000300014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apoptosis Proteins and Complement Components in the Etiopathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus is a prototypical autoimmune disease characterized by the deregulation of T and B cells, tissue infiltration by mononuclear cells, tissue damage and the production of autoantibodies. There is a consensus that accelerated apoptosis of circulating lymphocytes and/or impaired clearance of apoptotic bodies may increase the amount of nuclear antigens presented to T lymphocytes. This process is accompanied by autoimmune responses that can lead to the development of lupus. The dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 58 publications
1
18
0
2
Order By: Relevance
“…All of the SLE patients in this family tested positive for IgE. Studies have reported that IgE leads to abnormal immune reaction which is followed by IgE production by activated B cells [ 32 34 ]. Also, activated T cells that produce IL-4, IL-5, and IL-10 provide help to B cells, which differentiate into IgE secreting plasma cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the SLE patients in this family tested positive for IgE. Studies have reported that IgE leads to abnormal immune reaction which is followed by IgE production by activated B cells [ 32 34 ]. Also, activated T cells that produce IL-4, IL-5, and IL-10 provide help to B cells, which differentiate into IgE secreting plasma cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction due to the direct consequence of alterations in proteins/genes such as Fas, Bcl-2 and clq. [ 13 ]…”
Section: Apoptosis and Oral Lichen Planusmentioning
confidence: 99%
“…Recently, defects in apoptotic cells clearance leading to secondary cell necrosis and subsequent release of intracellular autoantigens has been proposed as one of the mechanisms of induction of these autoantibodies [ 3 ] [ 4 ]. According to this proposal, molecules of importance in the uptake of dying cells could have a role in host protection against autoimmune diseases, including SLE [ 5 ] [ 6 ] [ 7 ] [ 8 ].…”
Section: Introductionmentioning
confidence: 99%